A Case Study: Policy Communication at Postgraduate Program Academic Service of Public Service - Ismandianto; Faisyal Rani (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
This research aims at describing the factors influence the policy communication at Postgraduate Program Academic Service of Public Service unit of Politic and Social Science Faculty of Riau University. The method of this research is qualitative with purposive sampling technique used. The sample of the research is the persons who know and involved in the academic service of Politic and Social Science Faculty of Riau University. The data were collected by documentation, interview, and observation. The data were analysed by using descriptive qualitative technique which focus on the particular object intensively. The finding of the research shows that policy communication implementation in Academic Service Unit was poor. It caused by the unbalance ratio of lecturer and students, lack of facilities maintenance, and there is no Standard Operational Procedure (SOP) in administration implementation, and the lack of monitoring and evaluation quality applied by the Faculty management. The factors influenced this policy communication were facilities and infrastructures, qualified human resources availability, Standard Operational Procedure (SOP) availability, students’ capacity management, students’ study road map service availability, course service and course monitoring implementation availability